Flight Characteristics of UAP (Unidentified Aerial Phenomena) From The Perspective of Propulsion Principle–Flight Performance Derived from Propulsion Principle (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper elucidates the entity of UAP (Unidentified Aerial Phenomena) and its unique flight performance from the viewpoint of propulsion theory. Unidentified Aerial Phenomena (UAP) partially identified as being unknown anomalous aircraft, referred to as Unidentified Anomalous Vehicles (UAVs) or Unidentified Flying Objects (UFOs), have been observed globally. These unidentified craft typically exhibit anomalous flight characteristics, such as traveling at extremely high speeds, changing direction or accelerating at extremely high rates, and hovering motionless for long periods of time. UAP is a manned spacecraft capable of interstellar travel, and an aircraft that flies freely within the planet's atmosphere when it reaches the planet. The flight mechanism is the same principle as the gravity generation mechanism, and is derived from the acceleration generated by the curvature of space, that is, the curved space, which comes from the nature of space as a continuum.  From the perspective of space propulsion physics, this paper clarifies the substance of the UAP, including its propulsion principle, propulsion mechanism, and the characteristic flight performance of the UAP that is inevitably obtained therefrom.